Dynamics of changes in lipid peroxidation and antioxidant protection under the influence of complex treatment in patients with comorbid course of non-alcoholic steatohepatitis - O. Yu. Filippova (Zaporožskij Medicinskij Žurnal)
The aim to assess the effect of various complex treatment regimens on lipid peroxidation (LPO) and antioxidant protection (AOP) in patients with non-alcoholic steatohepatitis (NASH) in combination with obesity (OB) and biliary tract pathology (BT), based on 6-month follow-up data.